Comparison Between Calculated Speed-Based and Sensor-Fused Speed-Based Engine In-Cylinder Pressure Estimation Method. Issue 1 (2022) - Han, Runzhe; Bohn, Christian; Bauer, Georg
Abstract: This paper first proposes a recursive Kalman filter-based cylinder pressure estimation method using sensor-fused speed signal, and afterwards makes a comparison with previous results. In the proposed method of this paper, the fused engine speed is obtained using the centralized sensor fusion technique which synthesizes the information from engine vibration sensor and engine flywheel angular speed sensor. Cylinder pressure estimation results are evaluated by two combustion parameters which are pressure peak Pmax and peak location Ploc . The estimation results of the proposed method are obtained and compared with previous estimation results.